2016
DOI: 10.1097/ico.0000000000000979
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Microscopic Features of Keratoconic Corneal Morphology

Abstract: Purpose:To search for gold-standard histology indicators using alternative imaging modalities in keratoconic corneas.Methods:Prospective observational case–control study. Fourteen keratoconic corneas and 20 normal corneas (10 in vivo healthy subjects and 10 ex vivo donor corneas) were examined. Images of corneas were taken by spectral domain optical coherence tomography (SD-OCT) and in vivo confocal microscopy (IVCM) before keratoplasty. The same removed corneal buttons were imaged after keratoplasty with full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…However, in vivo confocal images showed abnormal features in every layer of the cornea, including abnormal epithelial and stromal keratocytes. 8 Microscopic features of keratoconic corneas indicated irregular arrangement in basal epithelial cells, 4,8 reduction in basal epithelial cell and keratocyte densities, 4,13 and epithelial apoptosis along with Histological and microRNA Signatures in Keratoconus/Wang et al corneal epithelium thinning. 9 Likewise in our study, the keratoconic corneal epithelial cells were loosely arranged ( Figure 1A) and significantly fewer in number compared to normal corneal epithelia ( Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo confocal images showed abnormal features in every layer of the cornea, including abnormal epithelial and stromal keratocytes. 8 Microscopic features of keratoconic corneas indicated irregular arrangement in basal epithelial cells, 4,8 reduction in basal epithelial cell and keratocyte densities, 4,13 and epithelial apoptosis along with Histological and microRNA Signatures in Keratoconus/Wang et al corneal epithelium thinning. 9 Likewise in our study, the keratoconic corneal epithelial cells were loosely arranged ( Figure 1A) and significantly fewer in number compared to normal corneal epithelia ( Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…After 14-days of culture, the cell sheet area grown on the scaffolds and on the AM were imaged non-invasively with full-field optical coherence microscopy (FFOCM, LLTech, France 40,41,42,43,44,45 ) to determine the number of cell layers grown on the carriers.…”
Section: Cell Culture Experimentsmentioning
confidence: 99%
“…They also showed that the posterior surface measurement was more reliable than with Scheimpflug technology [11]. New methods such as corneal OCT and topographic mapping of EP and BL have been proposed for early detection of keratoconus [12][13][14][15]. However, this requires high-resolution OCT technology in order to resolve EP and BL with sufficient precision.…”
Section: Keratoconusmentioning
confidence: 99%